Perceived fairness and consequences of affirmative action policies - Hannah Schildberg-Hörisch; Chi Trieu; Jana Willrodt (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
Debates about affirmative action often revolve around fairness. Accordingly, we document substantial heterogeneity in the fairness perception of various affirmative action policies. But do these differences translate into different consequences? In a laboratory experiment, we study three different quota rules that favor individuals whose performance is low, either due to bad luck (discrimination), low productivity, or choice of a short working time. Higher fairness perceptions coincide with a higher willingness to compete and less retaliation against winners. No policy harms overall efficiency or post-competition teamwork. Furthermore, individuals seem to internalize the normbehind the policies that are perceived as fairest.
Keywords: C91; D02; D63; 330; affirmative action; fairness ideals; experiment; tournament; real effort